2006
DOI: 10.1080/10550490600859892
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Tobacco Cessation Treatment into Mental Health Care for Patients with Posttraumatic Stress Disorder

Abstract: The integration of tobacco cessation treatment into mental health care for posttraumatic stress disorder (PTSD), known as Integrated Care (IC), was evaluated in an uncontrolled feasibility and effectiveness study. Veterans (N = 107) in PTSD treatment at two outpatient clinics received IC delivered by mental health practitioners. Outcomes were seven-day point prevalence abstinence measured at two, four, six, and nine months post-enrollment and repeated seven-day point prevalence abstinence (RPPA) obtained acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 61 publications
1
47
0
Order By: Relevance
“…16 Tobacco treatment randomized trials have had significant effects on long-term abstinence and have found that quitting smoking does not worsen clinical symptoms of unipolar depression, bipolar disorder, posttraumatic stress disorder, or schizophrenia. [17][18][19][20][21] Further, treatment of tobacco dependence was associated with a decreased likelihood of rehospitalization. 22 A review of cessation treatments for outpatients with mental illness concluded that for depressed smokers, cognitive-behavioral and nicotine replacement therapy (NRT) doubled cessation rates and reduced depressive symptoms.…”
Section: Introductionmentioning
confidence: 93%
“…16 Tobacco treatment randomized trials have had significant effects on long-term abstinence and have found that quitting smoking does not worsen clinical symptoms of unipolar depression, bipolar disorder, posttraumatic stress disorder, or schizophrenia. [17][18][19][20][21] Further, treatment of tobacco dependence was associated with a decreased likelihood of rehospitalization. 22 A review of cessation treatments for outpatients with mental illness concluded that for depressed smokers, cognitive-behavioral and nicotine replacement therapy (NRT) doubled cessation rates and reduced depressive symptoms.…”
Section: Introductionmentioning
confidence: 93%
“…Two recent studies evaluated tobacco treatments among smokers with current mental illness -one focused on clinically depressed smokers (S. M. and the other on veterans with post-traumatic stress disorder (McFall, et al, 2006). Both reported significant intervention effects for long-term smoking cessation with no adverse effects on mental health functioning (J. J.…”
Section: Or Diabetes (Diabetes Prevention Programmentioning
confidence: 99%
“…In a population of patients treated for opiate addiction who are maintained on methadone, the rates of chronic pain are reported at approximately 37 to 60 percent [50]. Alcohol and other substances are also commonly used to cope with the mental health effect of military deployment, including the selfmanagement of depression, anxiety, PTSD, and chronic pain [51][52]. It is also found that substance use disorders are underrecognized in those returning from deployment.…”
Section: Comorbid Disorders In Ptsd and Chronic Painmentioning
confidence: 99%